Extended view on the mechanobiology of fracture healing: interplay between mechanics and inflammation - Gläser, Nico; Schröder, Maria; Barcik, Jan; Haffner-Luntzer, Melanie; Wehrle, Esther (Frontiers in Bioengineering and Biotechnology, 2025)
It is well established that the biomechanical environment guides bone regeneration. It is also commonly accepted that the early inflammatory phase of fracture healing is decisive for the later regeneration process by inducing angiogenesis, stem cell invasion and cartilage and bone tissue formation. While traditionally, biomechanical orchestration and inflammation were viewed as distinct phenomena, recent research has illuminated the intricate relationship between mechanics and inflammation in the mechanobiology of fracture healing. In this review, we summarize the current knowledge of how mechanical stimuli influence bone regeneration by inducing tissue differentiation, and we broaden the perspective on the mechanobiology of fracture healing by incorporating recent insights into the interaction between mechanical forces and inflammation—an emerging field termed as “mechano-immunomics.” Key topics include the impact of fixation stiffness on immune cell migration and early gene expression of extracellular matrix-modulating genes, the influence of the mechanical environment within the early fracture hematoma on platelets and immune cells, and whether external biomechanical stimulation can alter the mechano-immunomic landscape. Gaining a deeper understanding of this dynamic interplay offers promising opportunities for innovative therapeutic strategies to enhance fracture healing. However, significant challenges remain, such as the development of suitable in vitro systems, well-characterized in vivo models, and effective interdisciplinary collaboration across the fields of biology, immunology, and biomechanics.